Effects of online brand communities on millennials' brand loyalty in the fashion industry. Issue 5 (2nd March 2021) - Ozuem, Wilson; Willis, Michelle; Howell, Kerry; Helal, Guida; Ranfagni, Silvia; Lancaster, Geoff
Abstract: Online brand communities are gaining traction in the development of marketing strategy, but it is unclear how the dominant group of users, the millennials, is being targeted with the prevailing and varying customer loyalty programs. Grounded in understanding that loyalty is seen and understood differently by people who participate in online brand communities, this study is based on a constructivist perspective combined with hermeneutic methodology and embedded case study research strategy to examine how online brand communities activate multidimensional customer loyalty intentions. Empirical data were generated through 45 in‐depth interviews of millennials. The analysis proposes a framework that categorizes customer loyalty into ambassador loyalists, public‐voting loyalists, loveless loyalists, and mercenary loyalists. Each stream contains one additional subcategory mediated by consumer levels of participation in online brand communities. This study contributes to existing literature. Unlike extant studies, it specifically argues that customers' loyalty intentions in online brand communities depend on the individuals and context, and it categorizes loyalty into different levels. Practical steps by which companies may utilize these categories and theoretical implications for wider consideration are proposed.